2010
DOI: 10.1152/jn.00174.2010
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Visual Feedback Affects Both Manual Tracking and Grip Force Control When Transporting a Handheld Object

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 57 publications
(79 reference statements)
5
58
3
Order By: Relevance
“…the mismatch between the hand and cursor is resolved by interpreting the cursor as a pulled mechanical load (e.g. spring-mass -damper system) [25]. Note that peak sensation at the 908 delay can be explained only by assuming a nondelayed trajectory of the hand separate from the delayed cursor.…”
Section: Discussionmentioning
confidence: 99%
“…the mismatch between the hand and cursor is resolved by interpreting the cursor as a pulled mechanical load (e.g. spring-mass -damper system) [25]. Note that peak sensation at the 908 delay can be explained only by assuming a nondelayed trajectory of the hand separate from the delayed cursor.…”
Section: Discussionmentioning
confidence: 99%
“…The hand-held object included two force sensors (ELPM-T1M-25N; Entran Devices, Fairfield, NJ). One force sensor measured the grip force (the force applied perpendicularly to the sensor surface) resulting from the combined action of the thumb and index finger (Danion and Sarlegna 2007;Sarlegna et al 2010). The other force sensor was used to measure the load force exerted vertically on the object.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, detrimental effects of optic flow have been already shown for other motor behaviors such as postural control (Guerraz and Bronstein 2008;Lestienne et al 1977;Thurrell and Bronstein 2002;Wei et al 2010) and arm movement control (Cohn et al 2000;Dvorkin et al 2009), whereas similarities between postural control and grip-force control have been reported (Wing et al 1997). Moreover, a recent experiment performed by our group has shown that despite access to (conflicting) cutaneous/proprioceptive information, delayed visual feedback provided by means of a computer screen was sufficient to alter the timing of feedforward gripforce modulations, possibly because subjects experienced illusory changes in object load (Sarlegna et al 2010). Following this scheme, it is plausible that, using immersive environment, downward accelerations of the visual scene should yield an illusion of upward motion of the elevator, leading to illusory increase in object load thereby associated with an increase in grip force.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…It was suggested that the misalignment between the hand and the cursor is interpreted as a mechanical load of mass (the cursor) with a spring and a damper that connects between the hand and the cursor. This model was used to explain the changes in grip forces accompanied with delayed visual feedback (Sarlegna et al, 2010), the changes in resistive sensation following adaptation to visuomotor delay (Takamuku and Gomi, 2015), and the generalization between adapting to a visuomotor delay or to a mechanical system between the hand and the cursor (Leib et al, 2017). In addition, representation of mechanical system also explains the changes in movements after adapting to force field (Wang et al, 2001).…”
Section: Adaptation and Representation Of Visuomotor Delaymentioning
confidence: 99%